2013
DOI: 10.1002/lary.24463
|View full text |Cite
|
Sign up to set email alerts
|

Application of an electronic nose in the diagnosis of head and neck cancer

Abstract: 3b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(103 citation statements)
references
References 36 publications
(52 reference statements)
2
98
0
Order By: Relevance
“…When coupled with multiple lines of recent data showing that exhaled H 2 S and urinary H 2 S is increased in cancer patients (as discussed earlier), it may possible that dogs sense cancer patients by detecting H 2 S. However, we believe that dogs detect a complex ''signature'' of various volatile molecules (including H 2 S). Such volatile signatures may be useful for the future detection of cancer, either by dogs or by various ''artificial nose'' systems currently under development (21,70).…”
Section: H 2 S Donation Versus H 2 S Biosynthesis Inhibition In Cancermentioning
confidence: 99%
“…When coupled with multiple lines of recent data showing that exhaled H 2 S and urinary H 2 S is increased in cancer patients (as discussed earlier), it may possible that dogs sense cancer patients by detecting H 2 S. However, we believe that dogs detect a complex ''signature'' of various volatile molecules (including H 2 S). Such volatile signatures may be useful for the future detection of cancer, either by dogs or by various ''artificial nose'' systems currently under development (21,70).…”
Section: H 2 S Donation Versus H 2 S Biosynthesis Inhibition In Cancermentioning
confidence: 99%
“…However, they did not attempt quantification, and their study group comprised only 11 laryngeal carcinoma patients and 10 healthy controls (García et al , 2014). Leunis et al (2013) have chosen the alternative approach and have attempted identifying the breath-print of HNSCC from exhaled breath samples, using a commercial sensor array and statistical pattern analysis software. They could distinguish HNSCC patients from a control group of patients having unspecified benign conditions with 90% sensitivity and 80% specificity.…”
mentioning
confidence: 99%
“…Other studies described possible volatile biomarkers in exhaled breath and the ability of electronic noses to recognize exhaled breath of patients suffering from malignant conditions in systems not involving the lungs and the respiratory system, such as breast, colon, prostate, and gastric cancer . Moreover, several studies analyzed the exhaled breath of patients with head and neck SCC as we did here . Using either electronic noses and GCMS, or electronic noses alone, these studies successfully generated differential diagnosis in advanced‐stage head and neck SCC (stage III/IV).…”
Section: Discussionmentioning
confidence: 88%
“…Several recent studies analyzed the exhaled breath of head and neck squamous cell carcinoma (SCC) patients and the capability of electronic noses to identify them . Most of these studies used profiling of the VOC fingerprint in the exhaled breath, and some suggested that specific compounds in the exhaled breath are possible volatile biomarkers for head and neck SCC .…”
Section: Introductionmentioning
confidence: 99%